2009
DOI: 10.2333/bhmk.36.149
|View full text |Cite
|
Sign up to set email alerts
|

Social Values on International Relationships in the Asia-Pacific Region

Abstract: Few studies on international politics have examined people's values, especially through use of cross-national analysis, although a country's foreign policy may reflect the values held by the public. The present paper examines results of the Asia-Pacific Values Survey and analyzes Asia-Pacific people's attitudes and values regarding international politics. Our focus is on three sets of items regarding people's attitude toward Japan, confidence in the United Nations, and ideology. First, we analyze response data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Thus, we can clearly recognize the distinctive clustering of results into Western and non-Western cultural spheres. As Figure 18 indicates, the pattern of distinctive clustering of results into Western and non-Western spheres can also be observed in the analysis of PRVS data, which is also claimed by Fujita and Yoshino (2009).…”
Section: Attitude Toward An International Organization: Confidence Insupporting
confidence: 61%
See 4 more Smart Citations
“…Thus, we can clearly recognize the distinctive clustering of results into Western and non-Western cultural spheres. As Figure 18 indicates, the pattern of distinctive clustering of results into Western and non-Western spheres can also be observed in the analysis of PRVS data, which is also claimed by Fujita and Yoshino (2009).…”
Section: Attitude Toward An International Organization: Confidence Insupporting
confidence: 61%
“…In contrast, in Australia, the percentage of those in their thirties or younger choosing Japan in APVS (around 5%) decreased compared to those in PRVS (around 10%). Although Fujita and Yoshino (2009) found that the younger age group in PRVS thinks Japan is diplomatically important, the pattern turns out not to be stable. Figure 5 shows the response distributions for Q.3 in APVS, while Figure 6 shows those in PRVS.…”
Section: Attitudes Toward Foreign Countriesmentioning
confidence: 84%
See 3 more Smart Citations